2000
DOI: 10.1002/(sici)1097-4644(20000401)77:1<82::aid-jcb9>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Multiple low-dose and single high-dose treatments with streptozotocin do not generate nitric oxide

Abstract: Streptozotocin (STZ) is a widely used diabetogenic agent that damages pancreatic islet beta cells by activating immune mechanisms, when given in multiple low doses, and by alkylating DNA, when given at a single high dose. Actually, STZ contains a nitroso moiety. Incubation of rat islets with this compound has been found to generate nitrite; moreover, photoinduced NO production from STZ has been demonstrated. These reports have suggested that direct NO generation may be a mechanism for STZ toxicity in diabetoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(23 citation statements)
references
References 36 publications
4
18
0
Order By: Relevance
“…Results of the present study revealed a significant increase in TBARS generation, accompanied by a significant decrease in the level of GSH (Figure 1) which indicate the ability of STZ‐induced diabetic nephropathy to modulate kidney oxidative status, and support the notion that STZ diabetic nephrotoxicity is associated with increased oxidative stress [40–42]. The contribution of FGH in prevention of renal oxidative stress induced by STZ is obvious in the present study (Figure 1).…”
Section: Discussionsupporting
confidence: 84%
“…Results of the present study revealed a significant increase in TBARS generation, accompanied by a significant decrease in the level of GSH (Figure 1) which indicate the ability of STZ‐induced diabetic nephropathy to modulate kidney oxidative status, and support the notion that STZ diabetic nephrotoxicity is associated with increased oxidative stress [40–42]. The contribution of FGH in prevention of renal oxidative stress induced by STZ is obvious in the present study (Figure 1).…”
Section: Discussionsupporting
confidence: 84%
“…Streptozotocin is selectively cytotoxic to pancreatic β-cells which damage beta-cells through the production of free radicals and involving with the cellular metabolic oxidative mechanisms [28]. Antioxidants can mitigate oxidative stress produced by STZ induced free radicals by neutralizing the available free radicals.…”
Section: Discussionmentioning
confidence: 99%
“…Streptozotocin is well reported for its selective pancreatic islet β-cell cytotoxicity [12] and has been widely used to induce diabetes mellitus in animals. Our results reveal that STZ injected rats exhibited significantly increased blood glucose levels as compared with control rats.…”
Section: Discussionmentioning
confidence: 99%